Preparation method and application of plasma modified molybdenum doped nickel sulfide
By preparing plasma-modified molybdenum-doped nickel sulfide electrocatalyst on nickel foam, the problem of difficulty in large-scale application of precious metal-based electrocatalysts is solved, and efficient hydrogen water decomposition and dye wastewater treatment are achieved, demonstrating the stability and applicability of this technology.
Patent Information
- Application Number
- CN202211209717.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-09-30
AI Technical Summary
The prior art is difficult to apply precious metal-based electrocatalysts on a large scale in commercial electrolysers, and a large amount of sewage is discharged in industrial production, especially in the printing and dyeing industry, making it difficult to efficiently treat dye wastewater.
By preparing plasma-modified molybdenum-doped nickel sulfide (Mo-Ni3S2) electrocatalyst on nickel foam, Mo ions are used to embed Mo-S interface parts of Ni3S2 nanoparticles to form an efficient and stable electrocatalyst for water decomposition and dye wastewater treatment.
It realizes efficient hydrogen water decomposition and dye wastewater treatment. The hydrogen evolution overpotential of the PA@Mo-Ni3S2/NF-200 electrode is 114mV, which can achieve 83.28% orange-yellow G dye degradation rate, showing the characteristics of being stable, inexpensive and suitable for large-scale applications.
Smart Images

Figure CN115672357B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a plasma modification method, and in particular to a preparation method and application of plasma modified molybdenum-doped nickel sulfide. Background Art
[0002] Fossil fuel resources are currently decreasing, and the use of fossil fuels also causes significant pollution to the environment, so the development of sustainable and environmentally friendly energy is essential for human survival. Hydrogen has excellent energy density and environmental compatibility, so it is an ideal solution to solve future energy problems. Sustainable hydrogen production can be achieved through electrochemical and photoelectrochemical water splitting, because both technologies benefit from abundant water resources and produce high-purity H2. Electrochemical water splitting can be used to produce clean hydrogen with zero carbon emissions. Platinum (Pt) is the most effective HER electrocatalyst with zero overpotential and multiple pH tolerance. However, the scarcity and high cost of precious metal-based electrocatalysts hinder their large-scale application in commercial electrolyzers. Therefore, it is necessary to design active, durable, cheap and easily available electrocatalysts to serve as effective electrode materials for HER.
[0003] Layered transition metal dichalcogenides (LTMDs), such as MoS2, WS2, and Ni3S2, have been studied as HER catalysts and have become the forefront of electrocatalysis. For HER in alkaline solutions, the kinetics is governed by the balance between the dissociation of water and the subsequent chemisorption of water-splitting intermediates. Experimental studies and density functional theory (DFT) calculations have shown that the uncoordinated Mo-S sites along the edges of MoS2 have high chemisorption capacity for hydrogen, and transition metals such as MoS2 and Ni3S2 have excellent HER performance. In the industrial production process, the discharge of a large amount of wastewater is inevitable, especially the wastewater from the printing and dyeing industry, which is large in volume and difficult to treat. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a preparation method of plasma-modified molybdenum-doped nickel sulfide, which can prepare an efficient and stable Mo-doped Ni3S2 electrocatalyst on nickel foam. In the Mo-doped Ni3S2 structure, Mo ions embedded in Ni3S2 nanoparticles form a large number of Mo-S interface sites, and water decomposition is prepared and carried out at different temperatures, and the water with the best hydrogen decomposition effect is used for the treatment of dye wastewater.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0006] A method for preparing plasma-modified molybdenum-doped nickel sulfide comprises the following steps:
[0007] Step 1: ultrasonically treating nickel foam in hydrochloric acid, ethanol and water respectively, and then vacuum drying;
[0008] Step 2: Add Na2MoO4·2H2O into ultrapure water and stir to dissolve;
[0009] Step 3: Add thiourea into the solution dissolved in step 2 and stir to obtain a clear solution;
[0010] Step 4: After cleaning the nickel foam surface, immerse it in a clear solution, then ultrasonicate it in water, perform a hydrothermal reaction at 180° C., and cool it to room temperature to obtain uniformly grown Mo-Ni3S2 / NF-180;
[0011] Step 5: Take out Mo-Ni3S2 / NF-180 from the solution, wash it with ultrapure water and ethanol three times to remove unreacted residues, and then dry it in a vacuum oven;
[0012] Step 6: Repeat steps 1 to 5 to prepare Mo-Ni3S2 / NF-200 and Mo-Ni3S2 / NF-220 at 200°C and 220°C, respectively;
[0013] Step 7: Cut a portion of the molybdenum-doped nickel sulfide synthesized at 200° C. and transfer it to the center of the dielectric barrier discharge reactor, and treat it under an alternating voltage to obtain PA@Mo-Ni3S2 / NF-200.
[0014] Preferably, in step 1, the upper and lower bottom surfaces of the nickel foam are 3 cm×3 cm in size and 2 mm in thickness.
[0015] Preferably, in step 1, the concentration of hydrochloric acid is 3 mol / L, the concentration of ethanol is 95%, and the ultrasonic treatment time is 15 min.
[0016] Preferably, in step 2, the mass of Na2MoO4·2H2O is 0.2 g, and the volume of ultrapure water is 40 mL.
[0017] Preferably, in step 3, the mass of thiourea is 0.2 g and the stirring time is 15 min.
[0018] Preferably, in step 4, the ultrasonic treatment time is 15 min and the hydrothermal reaction time is 16 h.
[0019] Preferably, the step five is drying in a vacuum oven at 80° C. for 8-12 hours.
[0020] Preferably, in step seven, the AC voltage is 70V and the processing time is 60s.
[0021] Preferably, a plasma-modified molybdenum-doped nickel sulfide is used to degrade orange G wastewater.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention grows Mo-doped Ni3S2 nanostructure arrays on 3D Ni foam as an efficient electrocatalyst. The PA@Mo-Ni3S2 / NF-200 electrode has a good nanostructure, uniform growth and enhanced charge transfer capability. The hydrogen evolution overpotential of the PA@Mo-Ni3S2 / NF-200 electrode is 114 mV.
[0024] (2) The present invention prepares an efficient and stable Mo-doped Ni3S2 electrocatalyst on nickel foam. In the Mo-doped Ni3S2 structure, Mo ions embedded in Ni3S2 nanoparticles form a large number of Mo-S interface sites, which are prepared and subjected to water decomposition at 200°C. The water-decomposed hydrogen with the best effect is used for the treatment of dye wastewater, which can be treated efficiently.
[0025] (3) The plasma of the present invention is combined with this catalyst to degrade the orange-yellow G dye. When the conductivity is 3 mS / cm, the voltage is 70 V, the initial dye concentration is 50 mg / L, and the pH is 3, a degradation rate of 83.28% can be achieved. This stable, inexpensive, and abundant electrocatalyst is suitable for large-scale water decomposition to produce hydrogen and to control environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 .XRD patterns of molybdenum-doped nickel sulfide synthesized at different temperatures and molybdenum-doped nickel sulfide modified by plasma;
[0027] Figure 2 XPS spectra of plasma-modified Mo-doped NiS: (a) full spectrum of PA@Mo-Ni3S2 / NF-200; (b) Mo 3d; (c) Ni 2p; (d) S 2p;
[0028] Figure 3 .(ah) is the SEM image of Mo-doped NiS synthesized at 200°C after plasma modification; (hi) is the EDS spectrum of PA@Mo-Ni3S2 / NF-200 in the selected area;
[0029] Figure 4 .(ab) TEM images of plasma-modified Mo-doped NiS; (c) HRTEM images of plasma-modified Mo-doped NiS; (d) Selected area electron diffraction pattern of plasma-modified Mo-doped NiS; (ei) Elemental mapping of plasma-modified Mo-doped NiS;
[0030] Figure 5 Electrochemical HER properties of the electrocatalyst in 1.0 M KOH solution (a) Scan rate 5 mV s -1 Polarization curves at 10 mA cm -2Overpotential corresponding to current density; (c) Tafel plots corresponding to each catalyst; (d) Electrochemical impedance spectroscopy (EIS) of various catalysts; Polarization curves at initial and after 1000 CV cycles (inset);
[0031] Figure 6 . Comparison of predicted and actual values of plasma degradation of Orange G;
[0032] Figure 7 .Effect of the interaction between initial concentration and pH on the degradation rate of Orange G in the combined system: contour plot; response surface;
[0033] Figure 8 .Effect of the interaction between initial concentration and voltage on the degradation rate of Orange G in the combined system: contour plot; response surface;
[0034] Fig. 9 .Effect of the interaction between initial concentration and conductivity on the degradation rate of Orange G in the combined system: contour plot; response surface;
[0035] Fig.10 .The effect of the interaction between solution pH and voltage on the degradation rate of Orange G in the combined system: contour plot; response surface;
[0036] Fig.11 .The interaction between pH and conductivity of the solution in the combined system on the degradation rate of Orange G: contour plot; response surface;
[0037] Fig.12 .The effect of the interaction between voltage and conductivity on the degradation rate of Orange G in a combined system: contour plot; response surface. DETAILED DESCRIPTION
[0038] 1. Experimental part
[0039] 1. Experimental reagents and instruments
[0040] Table 1 Experimental reagents
[0041]
[0042] Table 2 Experimental instruments
[0043]
[0044] 2. Sample characterization test
[0045] XRD patterns were obtained on a Bruker D8 Advance X-ray diffractometer with Cu Kα radiation. SEM images and EDS spectra were recorded with a Zeiss Gemini 300 microscope. High-resolution TEM and mapping analyses were performed using a JEOL JEM 2100F microscope. XPS spectra were obtained on a Thermo Kalpha photoelectron spectrometer.
[0046] 3. Material preparation method
[0047] A method for preparing plasma-modified molybdenum-doped nickel sulfide comprises the following steps:
[0048] Step 1: Cut the nickel foam with a thickness of 2 mm into pieces with a size of 3 cm×3 cm on the upper and lower bottom surfaces, and perform ultrasonic treatment in 3 mol / L hydrochloric acid, 95% ethanol and water for 15 min respectively, and then vacuum dry;
[0049] Step 2: Add 0.2 g of Na2MoO4·2H2O to 40 mL of ultrapure water and stir to dissolve;
[0050] Step 3: Add 0.2 g of thiourea into the solution dissolved in step 2 and stir for 15 min to obtain a clear solution;
[0051] Step 4: After cleaning the nickel foam surface, immerse it in a clear solution, then ultrasonicate it in water for 15 minutes, hydrothermally react it at 180° C. for 16 hours, and cool it to room temperature to obtain uniformly grown Mo-Ni3S2 / NF-180;
[0052] Step 5: Take out Mo-Ni3S2 / NF-180 from the solution, wash it with ultrapure water and ethanol three times to remove the unreacted residue, and then dry it in a vacuum oven for 10 hours;
[0053] Step 6: Repeat steps 1 to 5 to prepare Mo-Ni3S2 / NF-200 and Mo-Ni3S2 / NF-220 at 200°C and 220°C, respectively;
[0054] Step 7: Cut 1 cm×1 cm of the molybdenum-doped nickel sulfide synthesized at 200°C and transfer it to the center of the dielectric barrier discharge reactor, and treat it at an AC voltage of 70 V for 60 s to obtain PA@Mo-Ni3S2 / NF-200.
[0055] The plasma-modified molybdenum-doped nickel sulfide of the present invention is suitable for degrading orange G wastewater.
[0056] 4. Electrochemical test
[0057] The catalyst-loaded NF was tested in 1 M KOH by a three-electrode system, with the working electrode being a graphite rod and the reference electrode being an Ag / AgCl electrode, respectively. All initial data were calibrated using 85% iR compensation, and the potential of the reversible hydrogen electrode (RHE) was calculated using the following formula: E(vs.RHE) = E(vs.Ag / AgCl) + 0.197 + 0.059 × pH. Linear sweep voltammetry (LSV) and cyclic voltammetry (CV) were used to determine the activity of the catalyst for HER, respectively. Before recording, the 100 mVs -1 Scan until a stable cyclic voltammogram is obtained. -1 The linear sweep voltammetry curves were recorded at a scan rate of 1000 Ω and the Tafel slope was obtained by plotting the overpotential versus log(J) from the LSV curves. Electrochemical impedance spectroscopy (EIS) was performed in the frequency range of 0.01 to 10 5 Recorded in Hz.
[0058] 5. Response surface catalytic degradation of dyes
[0059] The Box-Behnken design (BBD) was used to analyze the degradation process of Orange G by DBD combined catalyst PA@Mo-Ni3S2 / NF-200. The decolorization rate of Orange G was taken as the response value, recorded as Y, and the concentration, pH, voltage and conductivity were taken as the action factors, recorded as A, B, C, and D respectively (Table 3). 29 groups of interactive experiments were designed to investigate the effects of the four factors on the degradation of Orange G and determine the optimal process conditions.
[0060] Table 3 Values and level ranges of each factor
[0061]
[0062] 2. Characterization and performance analysis of catalysts
[0063] 1. XRD analysis
[0064] Nickel foam was selected as the substrate due to its 3D macroporous structure, excellent electrical conductivity and various electrochemical properties that are beneficial to the target applications. First, ultrapure water, sodium molybdate, thiourea and clean nickel foam were placed in a stainless steel autoclave. The autoclave was operated at different temperatures of 180°C, 200°C and 220°C for 16 hours. During the reaction, Na2MoO4 was reduced, Ni was oxidized by thiourea, and after plasma shock, plasma-modified Mo-doped Ni3S2 arrays were formed. Nickel foam not only acts as a nickel source, but also as a skeleton to anchor the PA@Mo-Ni3S2 / NF-200 array. The surface of the resulting nickel foam is all black, indicating that the plasma-modified Mo-doped Ni3S2 array is uniformly formed. Figure 1The X-ray diffraction (XRD) patterns of the electrocatalysts prepared under various conditions are given. Figure 1 In addition to the obvious diffraction peaks of Ni at 44.3°, 51.6° and 76.2°, the peak at 21.5° can be assigned to the (101) plane, the peak at 30.9° to the (110) plane, the peak at 38.0° to the (003) plane, the peak at 49.5° to the (113) plane, the peak at 50.0° to the (211) plane, the peak at 55.0° to the (122) plane and the peak at 56.3° to the (300) plane. Although these peaks confirm the presence of Ni3S2, the diffraction peaks of molybdenum compounds are not obvious because they are covered by the Ni diffraction peaks, probably due to the partial doping of Mo into the Ni3S2 lattice, as observed in other metal-doped catalysts.
[0065] 2. XPS analysis
[0066] X-ray photoelectron spectroscopy (XPS) measurements were performed ( Figure 2 ) to identify the main constituent elements and characterize the chemical valence states of these elements. PA@Mo-Ni3S2 / NF-200 was selected as the target sample because it has a series of good electrochemical properties as an electrocatalyst. In addition to the C 1s and O 1s peaks, Ni 2p, Mo 3d and S 2p peaks were clearly observed, and the PA@Mo-Ni3S2 / NF-200 sample clearly showed the presence of Ni, Mo, S, C, and O elements ( Figure 2 a). Figure 2 bd are the Mo 3d, Ni 2p and S 2p high-resolution X-ray photoelectron spectra of the samples. Figure 2 b shows the typical Mo 3d fitting peaks of PA@Mo-Ni3S2 / NF-200, with Mo 3d peaks at 234.7 and 231.6 eV. 3 / 2 and Mo 3d 5 / 2 The peaks indicate the characteristic Mo in PA@Mo-Ni3S2 / NF-200 4+ Doping. Mo-doped Ni3S2 contains Mo that is missing in pure Ni3S2 samples. 4+ This indicates that Mo is mainly in the form of Mo 4+ In addition, the lower the binding energy, the lower the valence of Mo, which is beneficial to enhance the HER performance under alkaline conditions for PA@Mo-Ni3S2 / NF-200. Figure 2 c, which contains two strong peaks at 872.8 and 855.2 eV, corresponding to Ni2p 1 / 2 and Ni 2p 3 / 2 The binding energy of Ni in Ni3S2 is precisely indicated. 3+ and Ni 2+Two other satellite peaks were also observed, and the two broad peaks at 878.9 and 860.9 eV were consistent with the satellite peaks, corresponding to the vibrational peaks of Ni. Figure 2 d shows that the two peaks at 160.9 eV and 162.2 eV belong to S 2p 3 / 2 and S 2p 1 / 2 The peak at 168.0 eV is due to the production of sulfates by oxidation in air. All the results show that Ni3S2 and Mo 4+ There is a strong electronic interaction between them, thus establishing a coupled interface.
[0067] 3. SEM analysis
[0068] Figure 3 The SEM image and EDS spectrum of PA@Mo-Ni3S2 / NF-200 catalyst prepared with nickel foam support are shown. The SEM image of the PA@Mo-Ni3S2 / NF-200 sample formed after plasma modification at 200°C illustrates the specific morphology of the sample after synthesis. Figure 3 From the 3D skeleton of nickel foam shown in a, it can be seen that the originally smooth surface of nickel foam has become rough, with densely packed blanks growing on it ( Figure 3 bc). Through further magnification observation, it was found that these blank structures are actually composed of countless tiny nanorods piled together to form a nano forest ( Figure 3 dg), these nanorods uniformly agglomerated together and attached to the surface of nickel foam, and the entire surface of the Ni substrate was uniformly and densely covered. During the reaction, the porous three-dimensional (3D) Ni foam support not only served as a conductive network to anchor PA@Mo-Ni3S2 / NF-200, but also provided a Ni source for the formation of high-density branch-like PA@Mo-Ni3S2 / NF-200 nanosupports. In addition, due to the anisotropic growth characteristics of molybdate anions, the morphology of these catalysts was affected by MoO4 2- Therefore, the pure Ni3S2 catalyst prepared without Na2MoO4 is a uniform nanosheet rather than dendritic nanorods grown on the surface of Ni foam. The dendritic PA@Mo-Ni3S2 / NF-200 nanorods exhibit 3D anisotropy, and they connect to form a nanoforest. Figure 3 hi is the EDS spectrum of the selected area, which confirms the presence of Mo, Ni and S elements in the sulfide product.
[0069] 4. TEM analysis
[0070] Transmission electron microscopy and high-resolution transmission electron microscopy (HRTEM) were used to further explore the detailed morphology and crystal structure of the prepared PA@Mo-Ni3S2 / NF-200. Their individual structures are well formed, forming a nanorod structure. Figure 4 As shown in ab, the diameter of the dendritic PA@Mo-Ni3S2 / NF-200 nanorods is uniform. In contrast, the morphology of pure Ni3S2 is similar to that of thick nanosheets with smooth surfaces, indicating the important role of Mo cations in inducing the formation of dendritic Mo-doped Ni3S2 nanoforests. It is worth noting that Ni3S2 still has significant lattice spacing after doping with Mo, which can be confirmed by the HRTEM images of PA@Mo-Ni3S2 / NF-200. The lattice spacing of the (110) crystal plane is 0.29nm, the lattice spacing of the (003) crystal plane is 0.24nm, and the lattice spacing of the (113) crystal plane is 0.18nm ( Figure 4 c). In addition, the selected area electron diffraction (SAED) pattern of a single PA@Mo-Ni3S2 / NF-200 nanorod shows that the polycrystalline structure of PA@Mo-Ni3S2 / NF-200 has a ring-shaped polycrystalline structure ( Figure 4 d), which is consistent with pure Ni3S2. This further confirms that Mo has been successfully incorporated into Ni3S2 through doping. Elemental mapping analysis by energy dispersive X-ray spectroscopy combined with transmission electron microscopy (STEM-EDS) ( Figure 4 ei) clearly shows that Mo, Ni and S elements are uniformly distributed in the Mo-doped Ni3S2 sample.
[0071] 5. Catalytic performance of HER
[0072] The HER activity of the electrocatalysts was evaluated in alkaline solution (1 M KOH) using a standard three-electrode system. Figure 5 ), the effects of temperature and plasma modification on the hydrogen evolution reaction after adding Mo source were studied. The HER activity of Mo-Ni3S2 / NF-180, Mo-Ni3S2 / NF-200, Mo-Ni3S2 / NF-220, and PA@Mo-Ni3S2 / NF-200 were tested under the same conditions. In addition, the HER activity at a current density of 10 mA cm -2 The Tafel slope (log j-η) and overpotential at different times and electrochemical impedance spectroscopy (EIS) are used to estimate and compare the HER performance of electrocatalysts. Figure 5 As shown in a, PA@Mo-Ni3S2 / NF-200 has a small overpotential of 114 mV and can reach 10 mA cm -2 The current density is 134 mV dec. -1 . Figure 5b shows the overpotentials of other electrocatalysts Mo-Ni3S2 / NF-180, Mo-Ni3S2 / NF-200 and Mo-Ni3S2 / NF-220 (309, 267 and 145 mV), which are relatively high compared with them. Figure 5 c shows the Tafel slopes of other electrocatalysts as follows: 243, 227, and 147 mV dec for Mo-Ni3S2 / NF-180, Mo-Ni3S2 / NF-200, and Mo-Ni3S2 / NF-220, respectively. -1 . We attribute the excellent activity of PA@Mo-Ni3S2 / NF-200 to the in situ growth of the electrocatalyst on nickel foam without any binder. This approach, in addition to allowing uniform growth, enhances the mechanical adhesion and conductivity of the catalyst, placing it on a larger electrochemical surface area and a large number of active sites available for electrochemical redox reactions. Ionic and transport resistance are also important factors affecting the HER reaction in the electrolyte. To determine the role played by impedance in HER, we recorded the Nyquist plot ( Figure 5 d). The ion and charge transfer resistance values of the HER catalysts in 1M KOH electrolyte were obtained, which enabled us to interpret the reaction kinetics of the catalysts. The charge transfer resistance of PA@Mo-Ni3S2 / NF-200 was 1.395Ω, while the values of Mo-Ni3S2 / NF-180, Mo-Ni3S2 / NF-200 and Mo-Ni3S2 / NF-220 were slightly higher (4.477, 3.41 and 2.224Ω). The resistances obtained from the EIS spectra of the various catalysts showed that the impedance of PA@Mo-Ni3S2 / NF-200 was significantly lower, and thus the HER kinetics were significantly improved. And after 1000 cycles, the original catalytic performance was still maintained.
[0073] 6. Degradation of Orange G by Response Surface Methodology Combined System
[0074] (1) Model establishment
[0075] Using Design-Expert software, 29 experimental schemes were designed using BBD, and response surface design was performed on the degradation process of Orange G by DBD-PA@Mo-Ni3S2 / NF-200. The degradation time was set to 180s. Experiments were carried out according to each set of process conditions and the degradation rate of each set of degradation experiments was calculated. The results are shown in Table 4.
[0076] According to the results in Table 4, the empirical relationship between the response amount (Y-degradation rate) and the independent variables (A-concentration, B-pH, C-voltage, D-conductivity) can be obtained as the following second-order polynomial equation:
[0077] Y=58.27-6.23A+0.45B+4.98C-2.05D+2.49AB-1.54AC+2.67AD+0.97BC+0.79BD-0.52CD+4.55A 2 +14.05B 2 +1.08C 2 +2.95D 2
[0078] Table 4 Experimental design
[0079]
[0080]
[0081] (2) Analysis of variance
[0082] like Figure 6 As shown, the experimental data are relatively scattered, but they are evenly distributed in the left and right range of a straight line, which shows that the experimental value is close to the theoretical value, and there is a high correlation between the two, which proves that the experimental design idea is correct. There are some experimental operation errors, but they are within the controllable range. Table 5 is the variance analysis table of the degradation rate of orange-yellow G wastewater. When using plasma combined with PA@Mo-Ni3S2 / NF-200 to degrade orange-yellow G wastewater, the effects of the initial concentration, initial pH value, voltage and conductivity on the reaction alone, the interaction caused by the combination of the four factors, and the effect of the quadratic power of the four factors on the degradation rate of orange-yellow G are investigated. In the model established by the response surface method, the experimental effect is required to be effective, and it must be shown that the effect of the established response surface model is significant. In the data table, it is directly stated that the P value is less than 0.0001 and the F value is as large as possible. Comparing the F values of A, B, C, and D, A>C>D>B is obtained, which shows that the influence of a single factor on the degradation effect of orange-yellow G wastewater is initial concentration>voltage>conductivity>pH value. The F value of the model's lack of fit is 1.21, the model's lack of fit probability is 46.15%, and the lack of fit is not significant, indicating that the model is available. In addition, it can be seen from the data table that the P values of A and C in the first term are less than 0.0001, indicating that the initial concentration and voltage have a very significant impact on the degradation of orange-yellow G wastewater. The P value of AD is the smallest among them, proving that the interaction between initial concentration and conductivity has a better degradation effect on orange-yellow G wastewater, while the P values of other interactions are larger. The data analysis shows that the model is available, and it is concluded that the response surface model can truly show the degradation effect of orange-yellow G wastewater under the action of two-to-one interaction factors.
[0083] Table 5 Variance analysis table
[0084]
[0085] (3) Analysis of the interaction between plasma DBD and PA@Mo-Ni3S2 / NF-200 in the degradation of orange G
[0086] 1) The interaction between solution concentration and pH
[0087] Figure 7 The interactive effect between solution concentration and initial pH during the degradation reaction of orange-yellow G wastewater is shown. It can be concluded from the trend of the contour lines in the figure that the changes in the two in the experiment have a significant effect on the degradation rate of orange-yellow G, indicating that the interaction between the two in the treatment of orange-yellow G wastewater is significant, and the P value of AB is also the second smallest value in the interactive effect, thus verifying the conclusions described in the contour map. According to the height of the three-dimensional stereogram, the highest removal rate will occur above one of the four critical points, and the best degradation effect is obtained at low concentrations and acidic pH values. Due to the low concentration of the dye, the dye molecules can be fully adsorbed by the catalyst, and the acidic environment that is conducive to catalysis, the plasma can better combine with it to achieve the best degradation effect. Therefore, in the experiment, the treatment effect of orange-yellow G wastewater can be improved by maintaining a low initial concentration and lowering the pH value, and the optimal removal rate of orange-yellow G wastewater can be obtained.
[0088] 2) The interaction between solution concentration and voltage
[0089] Figure 8 The interactive effect between solution concentration and voltage during the degradation reaction of orange-yellow G wastewater is shown. Observing the contour map, the span of the contour value change is not large, and the P value of the initial solution concentration and voltage is slightly larger than 0.3228, indicating that the interaction between the two influencing factors in the experiment is not particularly significant. It can be seen from the contour map that the contour line values are basically blue and low, indicating that the removal rate of this part is low. In addition, it can be seen from the three-dimensional stereogram that the lower the concentration and the higher the voltage, the higher the degradation rate, which is obvious in the range of 82V and above. Therefore, when the initial pH of the solution is 7, the initial concentration of the solution is 50mg / L, the conductivity is 3mS / cm, and the voltage is greater than or equal to 82V, the optimal degradation rate of orange-yellow G wastewater can be obtained within this range.
[0090] 3) The interaction between solution concentration and conductivity
[0091] Fig. 9The interactive effect between the initial concentration and conductivity of the solution during the degradation reaction of Orange G wastewater is shown. According to the trend of the contour lines and the comparison with the three-dimensional stereogram, it is obvious that the lower the initial concentration, the smaller the solution conductivity, and the better the degradation efficiency of Orange G wastewater; this indicates that when the concentration is low, the number of dye molecules is small and it is easier to be degraded by plasma combined with catalyst. Low conductivity can make the free radicals generated by plasma move quickly and be utilized by the catalyst. On the contrary, too high conductivity will make the free radical molecules move faster in the solution and fail to successfully combine with the catalyst, resulting in a lower degradation rate. Therefore, it can be concluded that under the conditions of a voltage of 70V and an initial pH value of 7, when the initial concentration is 50mg / L and the solution conductivity is 1mS / cm, a better degradation efficiency of Orange G wastewater can be obtained.
[0092] 4) The interaction between solution pH and voltage
[0093] Fig.10 It mainly shows the mutual influence of pH value and voltage in the experiment. As can be seen from the contour map, the shape of the contour line is almost semi-elliptical, with a large arc, and the interaction of this influencing factor is more significant. More active substances such as free radicals can be produced under high voltage, and the catalyst can better utilize its active substances under suitable alkaline conditions, so as to better degrade. It can be seen from the three-dimensional stereogram that the highest area of the stereogram is on both sides. Compared with the contour map, it can be seen that this part is in the upper right corner and the color is slightly orange-red, indicating that its degradation effect is better. Therefore, under the conditions of initial concentration of 125mg / L and conductivity = 3mS / cm, when the pH value is 11 and the voltage is 90V, a better degradation efficiency of orange-yellow G wastewater under the conditions of this influencing factor can be obtained.
[0094] 5) The interaction between solution pH and conductivity
[0095] Fig.11It reflects the interactive effect of pH value and conductivity in the treatment of orange-yellow G wastewater. The P value of the interaction between pH value and conductivity is 0.6090, indicating that the two influencing factors are not particularly significant. From the contour map, it can be seen that the influence of pH value and conductivity on the experiment is symmetrical with pH=7 as the boundary. In the entire contour map, there is almost no red area. It can be seen that under the interactive influence of these two factors, the overall degradation efficiency is not high. From the three-dimensional stereogram, it can be seen that as pH and conductivity change from low to high, the degradation rate of orange-yellow G wastewater also fluctuates. At high pH and low conductivity, a relatively high degradation rate is obtained. Therefore, in order to improve the degradation rate of orange-yellow G wastewater, it is necessary to properly control the pH value at around 11 when the solution conductivity is low. When the initial concentration is 125mg / L, the voltage is 70V, the pH value is around 11, and the conductivity is 1mS / cm, the removal rate of orange-yellow G wastewater is relatively high.
[0096] 6) Interaction between voltage and conductivity
[0097] Fig.12 It reflects the interactive effect of voltage and conductivity in the treatment process of orange G wastewater. The P value of both voltage and conductivity is 0.7360, which is large and the effect is not significant. The flat trend of the three-dimensional graph also shows that the interactive effect of this factor is not particularly significant. Fig.12 It can be seen that the influence of voltage and conductivity on the experiment is similar, and the influence is not obvious. Under high voltage, lower conductivity has a higher degradation rate. It can be seen from the three-dimensional graph that under the conditions of initial concentration of 125mg / L, pH value of 7, voltage of 90V, and conductivity of 1mS / cm, the degradation rate of orange-yellow G wastewater is relatively high. Therefore, under the condition of certain conductivity, increasing the voltage appropriately will improve the treatment effect of orange-yellow G wastewater, but it should not be too high to reduce energy consumption.
[0098] The invention discloses a Ni3S2 nanostructure array doped with Mo grown on 3D Ni foam as an efficient electrocatalyst, and analyzes the morphology, composition and performance of the Mo-doped Ni3S2 catalyst modified by plasma. The PA@Mo-Ni3S2 / NF-200 electrode has a good nanostructure, uniform growth and enhanced charge transfer capability, and the hydrogen evolution overpotential of the PA@Mo-Ni3S2 / NF-200 electrode is 114mV. Plasma is combined with the catalyst to degrade orange-yellow G dye, and the four influencing factors selected in the experiment are analyzed by response surface method. The quadratic polynomial model established with the removal rate as the response value is highly significant. From the variance analysis of the fitting equation, it can be seen that the order of influence of the four single factors on the degradation effect of orange-yellow G wastewater is: initial concentration>voltage>conductivity>pH value; when the influencing factors interact, the interaction between the initial concentration and the conductivity has a certain significant effect, the interaction between the initial concentration and the pH value is relatively significant, and the other influencing factors are not significant, and the overall degradation effect of the dye is very good. Comprehensively considered, the optimal conditions are when the conductivity is 3mS / cm, the voltage is 70V, the initial dye concentration is 50mg / L, and the pH is 3, the degradation rate can reach 83.28%. The stable, cheap, and abundant electrocatalyst produced by the present invention is suitable for large-scale water decomposition hydrogen production and environmental pollution control.
Claims
1. A method for preparing plasma-modified molybdenum-doped nickel sulfide, characterized in that: Here are the steps: Step 1: ultrasonically treat the nickel foam in hydrochloric acid, ethanol and water for 12-18 minutes respectively, and then vacuum dry; Step 2: Add 0.2 g Na2MoO4·2H2O to 40 mL ultrapure water and stir to dissolve; Step 3: Add 0.2 g of thiourea into the solution dissolved in step 2 and stir for 12-18 minutes to obtain a clear solution; Step 4: After cleaning the nickel foam surface, immerse it in a clear solution, perform ultrasonic treatment in water for 12-18 minutes, then perform hydrothermal reaction at 200° C. for 14-18 hours, and cool to room temperature to obtain uniformly grown Mo-Ni3S2 / NF-200; Step 5: taking out Mo-Ni3S2 / NF-200 from the solution, washing it with ultrapure water and ethanol three times respectively to remove unreacted residues, and then drying it in a vacuum furnace to obtain molybdenum-doped nickel sulfide; A portion of the molybdenum-doped nickel sulfide is cut and transferred to the center of a dielectric barrier discharge reactor, and treated under an AC voltage for 50-70s to obtain PA@Mo-Ni3S2 / NF-200; the AC voltage is 70V.
2. The method for preparing plasma-modified molybdenum-doped nickel sulfide according to claim 1, characterized in that: In the step 1, the upper and lower bottom surfaces of the nickel foam are 3 cm×3 cm in size and 2 mm in thickness.
3. The method for preparing plasma-modified molybdenum-doped nickel sulfide according to claim 1, characterized in that: In the step 1, the concentration of hydrochloric acid is 3 mol / L, and the concentration of ethanol is 95%.
4. The method for preparing plasma-modified molybdenum-doped nickel sulfide according to claim 1, characterized in that: The temperature in the vacuum furnace in step 5 is 80°C.
5. The method for preparing plasma-modified molybdenum-doped nickel sulfide according to claim 1, characterized in that: The upper and lower bottom surfaces of the molybdenum-doped nickel sulfide cut in step 5 are 1 cm×1 cm in size.
6. Use of plasma-modified molybdenum-doped nickel sulfide prepared by the method for preparing plasma-modified molybdenum-doped nickel sulfide according to claim 1 in electrocatalytic degradation of orange G wastewater.
Citation Information
Patent Citations
Foamed nickel loaded nano flower-shaped nickel sulfide-molybdenum sulfide catalyst as well as preparation method and application thereof
CN114481203A